Изучение структуры дентина дна полости зуба под действием реминерализующего препарата «БВ» с помощью электронной сканирующей микроскопии (LLC "Endo Press", 2020)
In the conducted study was examined the dentine structure at the bottom of the tooth cavity after application of the remineralized medicine BV under scanning electronic microscope control. It was analyzed a 12 teeth, extracted on clinical indications. It was revealed that under remineralized therapy the bottom of the tooth cavity was hardened.